Tumour markers - Dragana Puhalo-Sladoje; Dragana Tošović; Slavica Ristić (Биомедицинска истраживања, 2013)
Many structures found in tumour cells acting like antigens have been discovered as a result of continuous progress in malignant disease research over the last 50 years. Those are macromolecules whose presence or change in concentration can indicate genesis or growth of malignant tumours and they are known as tumour markers. They can be highly specific, characteristic of only one type of tumours or they can be found in malignant cells of different tumours. They are often present inside normal cells, as well, either in some phases of cell development (in embryonic phase), or in reduced quantities, or undetected which, after being detected, become available to the immune system cells. These antigens are known by a common name - tumour associated antigens - and they are not characteristic of only one tumour, but they react with a large number of malignantly transformed cells as well as with some normal cells. Nevertheless, due to their reacting with malignant cells (and sometimes primarily with them), they are often used for diagnostic purposes. A number of clinically applied and routinely determined tumour associated antigens have been described so far. In Table 1, we can see an outline of markers in tumours inside different organs. Although highly diagnostically sensitive and specific, tumour markers, which could be used to diagnose cancer in asymptomatic population have not yet been discovered, their relia bility in monitoring oncological patients justifies their clinical application. National Academy for Clinical Biochemistry (NACB) gave special recommendations for clinical application of tumour markers in cases of lung cancer (Table 2).
Keywords: tumour markers; clinical application